Investigation of College Students’ Perception of Boredom and Loneliness Level in Leisure Time Activities during Covid-19 - Temel, Abdullah Sencer; Tükel, Yalçin (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The Covid-19 virus has affected every aspect of life on a large scale, specifically on people’s social and psychological leisure behaviour. And it led people to make certain changes to their lifestyles, habits and human relations at a large scale. Aim: Our study aimed to compare individuals’ levels of boredom and loneliness regarding active sport status, social, artistic and cultural activities in leisure time before and during the period of Covid-19. Methods: A purposeful sampling technique and a non-probabilistic sampling method were applied in determining the individuals in the study group. Data were collected through online questionnaire form. The sample group of this research constitutes 799 participants in different age groups. Results: The initial indication of the study stated that the participants’ perception of boredom in leisure time and their loneliness levels were high during Covid-19. In the study’s major findings, it was observed that participants who were involved in active sports, social, artistic and cultural activities before and during Covid-19 had a low level of boredom perception and loneliness levels during leisure time.. Conclusion: In the regression analysis, all sub-dimensions of the leisure boredom scale have a significant relationship with individuals’ level of loneliness during Covid-19 (p<0.05). As a result, the loneliness levels of individuals positively affect their perception of being bored during leisure time.